The Reformation Revised? The Contested Reception of the English Reformation in Nineteenth-Century Protestantism. Issue 1 (1st April 2014) - Nockles, Peter
Abstract : This article charts and discusses the reasons for various significant shifts and developments during the nineteenth century of the reception of the Reformation amongst different denominations and groups within British Protestantism. Attitudes towards Foxe's 'Book of Martyrs' are explored as but one among several litmus tests of the breakdown of an earlier fragile consensus based on anti-Catholicism as a unifying principle, with the Oxford Movement and the intra-Protestant reaction to it identified as a crucial factor. The selfidentity of the various British Protestant denominations, notably the various Nonconformist bodies as well as the established Church and evangelicalism per se was at stake in the process of 'reception'. Moreover, the emergence of more secular Protestant understandings of the significance of the Reformation as an essential stage in the emergence of modernity and liberty, often at odds with nineteenth-century evangelical theological interpretations of its meaning and legacy, are also highlighted. The result is an attempt to transcend the traditional focus on Protestant-Catholic disputes over the Reformation in narrowly bipolar terms.